THE USE OF JAVANESE TABOO WORDS IN MOVIE ENTITLED PUNK IN LOVE - SHABRINA, ZAHRA APRILLIQA MULKI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: taboo words, “Punk in Love” movie. In society, people know that using taboo words is forbidden, because taboo words are considered vulgar, but they still use it in communication. Most people use taboo when they are angry, but in East Java especially in Surabaya and Malang people can express happiness by using taboo words. They can use taboo words for their friend zone as a sign of familiarity. This study deals with the Javanese taboo words in the movie entitled “Punk in Love”. The writer chose this topic because all characters in the movie use taboo words. The objectives of this study are to find out Javanese taboo words in Punk in Love movie, to classify types of Javanese taboo words in Punk in Love movie and to find out the purposes of using Javanese taboo words in Punk in Love movie. This study is a qualitative study with document analysis, because the data were taken from the script of Punk in Love movie. The data of this study were the utterances containing taboo words produced by all characters (main characters and supporting characters) in Punk in Love movie and used Wardhaugh’s (2006) theory to analyze the data. The writer found 82 taboo words, consisting of 81 taboos uttered by the main characters and 1 taboo uttered by the supporting character. The main characters never use the left hand (the origin of sinister) term and religious manner term. The supporting characters only uttered 1 taboo word sex term and they never use other types of taboo words. The writer also found out that the use of taboo words has many purposes. All characters in this movie tend to use taboo words when they talk with each other to express their frustration. The writer suggests the next writer to conduct the research on taboo words using other theory and analyze in other objects such as in daily communication or in punker’s real life.